1955
DOI: 10.1071/ph550508
|View full text |Cite
|
Sign up to set email alerts
|

Rotation and Other Motions of the Magellanic Clouds from Radio Observations

Abstract: The radial velocities measured in a survey of the 21 cm line from the Magellanic Clouds are discussed, principally in terms of the median velocity for each line profile. It is shown that each Cloud is rotating, and the analysis confirms the view, based on optical evidence, that the Clouds are flattened and tilted systems. The gas is probably the least flattened constituent of each Cloud and shows a large decrease of rotational speed with increasing distance from the equatorial plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1955
1955
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 7 publications
(8 reference statements)
1
22
0
Order By: Relevance
“…The centroid of the 3·5 m distribution in the Large Cloud has been calculated by making reasonable estimates of the percentage of radiation originating in the outer regions and is probably accurate to about half a degree. Ignorance of the distribution of weak radiation far from the centre is the chief cause of" (1955a) and Kerr and de Vaucouleurs (1955). " All the centres differ in position, but in view of the uncertainties involved no definite conclusions can be drawn.…”
Section: Radiation From the Magellanic Oloudsmentioning
confidence: 99%
“…The centroid of the 3·5 m distribution in the Large Cloud has been calculated by making reasonable estimates of the percentage of radiation originating in the outer regions and is probably accurate to about half a degree. Ignorance of the distribution of weak radiation far from the centre is the chief cause of" (1955a) and Kerr and de Vaucouleurs (1955). " All the centres differ in position, but in view of the uncertainties involved no definite conclusions can be drawn.…”
Section: Radiation From the Magellanic Oloudsmentioning
confidence: 99%
“…Because astrophysical factor D depends only in the amount of DM in the halo, and is less sensitive to profile shape, calculations for dIrr Galaxies, plus a combined analysis, can improve our limits for τ χ . As an example, the astrophysical factor D for IC10 is 4.1631 × 10 15 TeV cm −2 , comparable to the value for Triangulum II.…”
Section: Pos(icrc2017)897mentioning
confidence: 54%
“…With the proof that Large and Small Magellanic Clouds are rotating systems [14,15], measurements of the rotation curve of other dIrr Galaxies were performed. It was observed that the rotation curve for these galaxies flatten after about 2 disk scale lengths and no cases of declining curves were found, indicating that dIrr Galaxies have no bulge.…”
Section: The Dm Profile In Dirr Galaxiesmentioning
confidence: 99%
“…4 The average value for the Clouds is approximately equal to the relative density in the solar neighborhood, but is much higher than the integrated figures for the Galaxy and M31. This difference conforms with the difference in galactic types, the Clouds being irregular, and presumably "younger" systems.…”
mentioning
confidence: 81%